De novo and inherited dominant variants in U4 and U6 snRNA genes cause retinitis pigmentosa - Quinodoz, Mathieu; Rodenburg, Kim; Cvackova, Zuzana; Kaminska, Karolina; de Bruijn, Suzanne E; Iglesias-Romero, Ana Belén; Boonen, Erica G M; Ullah, Mukhtar; Zomer, Nick; Folcher, Marc; Bijon, Jacques; Holtes, Lara K; et al. (Nature genetics, 2026)
Small nuclear RNAs (snRNAs) combine with specific proteins to generate small nuclear ribonucleoproteins (snRNPs), the building blocks of the spliceosome. U4 snRNA forms a duplex with U6 and, together with U5, contributes to the tri-snRNP spliceosomal complex. Variants in RNU4-2, which encodes U4, have recently been implicated in neurodevelopmental disorders. Here we show that heterozygous inherited and de novo variants in RNU4-2 and in four RNU6 paralogs (RNU6-1, RNU6-2, RNU6-8 and RNU6-9), which encode U6, recur in individuals with nonsyndromic retinitis pigmentosa (RP), a genetic disorder causing progressive blindness. These variants cluster within the three-way junction of the U4/U6 duplex, a site that interacts with tri-snRNP splicing factors also known to cause RP (PRPF3, PRPF8, PRPF31), and seem to affect snRNP biogenesis. Based on our cohort, deleterious variants in RNU4-2 and RNU6 paralogs may explain up to ~1.4% of otherwise undiagnosed RP cases. This study highlights the contribution of noncoding RNA genes to Mendelian disease and reveals pleiotropy in RNU4-2, where distinct variants underlie neurodevelopmental disorder and retinal degeneration.
Keywords: Ribonucleoproteins, Small Nuclear; rodokmen; Spliceosomes; retinopathia pigmentosa; Humans; dominantní geny; ženské pohlaví; malý jaderný ribonukleoprotein U4-U6; Genes, Dominant; RNA, Small Nuclear; Female; Male; mužské pohlaví; ribonukleoproteiny malé jaderné; Pedigree; Retinitis Pigmentosa; RNA malá jaderná; mutace; spliceozomy; Mutation; Ribonucleoprotein, U4-U6 Small Nuclear; lidé